Living with Recurrent Diabetic Foot Ulcers: A Phenomenological Study of Patients Receiving Home Care Wound Management - Parliani Parliani; Cau Kim Jiu; Deni Aryadi; Tri Wahyuni (Universitas Pahlawan Tuanku Tambusai, 2026)
Background: RDFU are a chronic complication of diabetes mellitus that affects patients’ physical, psychological, social, and spiritual well-being. Although home-based wound care services have expanded, patients’ lived experiences remain insufficiently explored. This study aimed to explore the lived experiences of patients with RDFU receiving wound care management. Methods: A qualitative study using an IPA) design was conducted at Maizar Wound Care Clinic, West Kalimantan, Indonesia, from March to December 2023. Participants included two patients with RDFU, one family caregiver, and two home care nurses, selected through purposive sampling. Data were collected through repeated semi-structured interviews and field notes and analyzed using the IPA framework. Results: Four themes emerged: physical limitations and loss of normality; changes in family and social roles; comfort and hope through home care services; and limited understanding of recurrence prevention. Family support and therapeutic relationships with nurses facilitated patients’ adaptation to their chronic condition. Conclusion: Holistic, patient- and family-centered home care enhances comfort, access to care, hope, and adaptation among patients with RDFU. Recommendation: Strengthening family-based home care and continuous DFU education is essential to prevent recurrence. Future studies should involve diverse participants and evaluate the long-term effectiveness of home care interventions.